Konsep Aplikasi Mobile Pembelajaran dan Media Sosial pada Pembelajaran Pendidikan Agama Islam - Andri Antoni (Cendekia, 2023)
This research aims to explain the concept of using mobile learning applications and social media in Islamic Religious Education learning. Along with the increasingly rapid development of information and communication technology and the availability of various social media, this can be used as an effective and efficient learning media in learning Islamic Religious Education. The type of research in this article is included in library research, where the data sources come from books and articles. Meanwhile, the research method used is descriptive analysis. The data analysis technique used in this research is content analysis, in the form of opinions from trusted sources. The results of this research show that there are many applications that can be used as mobile learning-based PAI learning media, both in the form of interactive visuals and interactive audio-visuals through various applications. The use of social media, especially Facebook, WhatsApp, Instagram, and YouTube as media in learning has proven effective and successful. The use of mobile learning applications and social media as learning media for Islamic Religious Education not only makes the learning process more interesting and communicative but can also be a solution for achieving learning goals.